Game Edukasi Pengenalan Rambu-Rambu Lalu LintasUntuk Anak SD - Andriyanto, Irwan, Prof. Dr. Budi Murtiyasa, M.Kom (2016)
Traffic signs is a sign that in pairs to provide information to road users , has the goal to improve security and the smooth road. To the authors would like to introduce some of the traffic signs on the road to elementary school children in order to implement in everyday life by displaying all kinds of traffic signs , as well as tips to use when on the road. Educational game introduction of traffic signs can provide the ease in acquiring knowledge about traffic signs and theory with ease . In addition to their entertainment also get knowledge Keywords : the introduction of traffic signs for elementary school children, educational games , Construct 2